2017
DOI: 10.3390/ijms18030608
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Molecular Mechanism of Non-Coding RNAs in Pathological Cardiac Remodeling

Abstract: Non-coding RNAs (ncRNAs) are a class of RNA molecules that do not encode proteins. Studies show that ncRNAs are not only involved in cell proliferation, apoptosis, differentiation, metabolism and other physiological processes, but also involved in the pathogenesis of diseases. Cardiac remodeling is the main pathological basis of a variety of cardiovascular diseases. Many studies have shown that the occurrence and development of cardiac remodeling are closely related with the regulation of ncRNAs. Recent resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 95 publications
1
41
0
Order By: Relevance
“…Non-coding RNAs (ncRNAs), which include miRNAs, long ncRNAs and circRNAs, are involved in the development of several diseases including pathological cardiac remodeling, nervous system diseases and several cancers (16)(17)(18)(19). circRNAs are a novel type of ncRNA characterized by a stable structure and highly specific tissue expression.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs), which include miRNAs, long ncRNAs and circRNAs, are involved in the development of several diseases including pathological cardiac remodeling, nervous system diseases and several cancers (16)(17)(18)(19). circRNAs are a novel type of ncRNA characterized by a stable structure and highly specific tissue expression.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic role of miRNA was first reported in chronic lymphocytic leukemia where the miRNA cluster, miR-15a/16–1, is frequently lost, thereby acting as a tumor suppressor [ 58 ]. Later, many transcriptome studies have shown that miRNA are aberrantly expressed both in various human cancers and other diseases like cardiological and neurological ones [ 56 , 59 , 60 ]. Moreover, since miRNA expression profiling is able to differentiate between normal and pathological states they could be used as novel biomarkers in the diagnosis and prognosis of several human diseases.…”
Section: Novel Insights From Transcriptome Studies By Next Generatmentioning
confidence: 99%
“…Besides, since many lncRNAs are antisense transcripts, the construction of directional libraries has allowed their better detection and discrimination from mRNA; so far, many different methods have been developed to preserve the orientation of the original RNA in the final sequencing library, and to facilitate strand-specific analysis of the resulting data [ 67 , 68 ]. As for the other ncRNA, even the deregulation of numerous lncRNA has been observed in many human diseases, from cancer to cardiac pathologies or neurodegenerative disorders [ 59 , 60 , 64 ]. For instance, among the others, the well-known MALAT1 , one of the first lncRNAs to be associated with a human disease, was initially described as metastasis associated in lung adenocarcinoma transcript; then further studies demonstrated that it is involved also in other disorders such as diabetes complications, since its expression was found to be augmented in ischemic limbs [ 60 ].…”
Section: Novel Insights From Transcriptome Studies By Next Generatmentioning
confidence: 99%
“…28 Our results, demonstrating associations of the lncRNAs MHRT, lncRNAs are involved in the regulation of cardiac remodelling via several different mechanisms, suggesting they represent potential therapeutic targets for the treatment of cardiac hypertrophy, heart failure and other cardiac disorders. 9,16,29,30 The manipulation of cardiac-related lncRNAs represents a new avenue for controlling the gene regulatory networks that are involved in cardiac diseases. MHRT, FENDRR and CARMEN could potentially represent attractive targets for future therapeutic strategies.…”
Section: Sion Inhibition Of Pathological Lvh Is An Attractive Therapmentioning
confidence: 99%